Strengthening the Character of the Integrative Moral-Based Muhammadiyah da'wah Movement as a Preventive Design for Student Anarchist Demonstrations - Suardi Suardi; Nursalam Nursalam; Shahrin Bin Hashim; Hasnah Kanji (JED (Jurnal Etika Demokrasi), 2023)
In order to avoid student anarchist demonstrations, a more thorough character-building programme is needed. The study's key issue is the unruly behaviour of the students who always participate in them. A model of Muhammadiyah character reinforcement was created as part of the research with the intention of preventing anarchist student protests at Muhammadiyah University of Makassar. This study employs a variety of research techniques. (Mixed techniques). The first stage employs qualitative research techniques, whereas the second stage combines quantitative and qualitative techniques. Quantitative research tools use validated lifts, whereas qualitative research tools mostly use the researchers themselves. Purposive sampling is used in qualitative research to identify research informants, whereas random sampling is used to choose research samples. Lifting, observation, interviews, and documentation are used as data collection approaches. Quantitative data analysis approaches utilise questionnaire verification, data tabulation, and percentage data questionnaires, whereas qualitative data analysis techniques use data reduction, display, and verification procedures. While quantitative data is validated using dependability (accuracy) and validity tests, qualitative data is validated using source triangulation and triangulation procedures. (benar). The study's findings demonstrated that habitus transmission, habitus reception, and collective habitus are used to strengthen the movement's character among students at Muhammadiyah University Makassar so that they participate in community and Muhammadiyah activities there. Attempts to stop anarchist demonstrations include strengthening the anarchist movement's reputation.